Industrial applications of fungal lipases: a review - Kumar, Ashish; Verma, Vinita; Dubey, Vimal Kumar; Srivastava, Alok; Garg, Sanjay Kumar; Singh, Vijay Pal; Arora, Pankaj Kumar (Frontiers in Microbiology, 2023)
Fungal lipases (Triacylglycerol acyl hydrolases E.C. 3.1.1.3.) are major industrial enzymes and have several applications in various industries and fields. Fungal lipases have been found in several species of fungi and yeast, and these enzymes are carboxylic acid esterases and come under the serine hydrolase family and do not require any cofactor for catalyzing the reactions. It was also noticed that processes like extraction and purification of lipases from fungi are comparatively easy and cheaper than other sources of lipases. In addition, fungal lipases have been classified into three chief classes such as GX, GGGX and Y. Lipases have applications not only in the hydrolysis of fats and oils (triglycerides) but also involve in synthetic reactions such as esterification, acidolysis, alcoholysis, interesterification and aminolysis. The production and activity of fungal lipases are highly affected by the carbon source, nitrogen source, temperature, pH, metal ions, surfactants as well as moisture content. Moreover, fungal lipases have several biotechnological applications in many fields such as biodiesel production, ester synthesis, production of biodegradable biopolymers, formulations of cosmetics and personal care products, detergent manufacturing, degreasing of leather, pulp and paper production, textile industry, biosensor development, drug formulations and as a diagnostic tool in the medical sector, biodegradation of esters, and bioremediation of wastewater etc. The immobilization of lipases onto different carriers also helps in improving the catalytic activity of lipases by increasing thermal and ionic stability (in organic solvents, high pH and temperature), easy in recycling, volume-specific loading of enzyme on support and thus these features have made appropriate for attaining the great attention to use as biocatalyst in various sectors.